Structure of nitrous oxide-carbon dioxide alloys - Solodovnik, A.A.; Danchuk, V.V. (Физика низких температур, 2009)
Structure of N₂O–CO₂ solid mixtures was investigated by transmission electron diffraction over the entire range of their mutual concentrations. In the temperature range 5–65 K the experimental data indicate no phase separation in these alloys. The average structure of the solutions belongs to the Pa3 symmetry. The behavior of the concentration dependence of the lattice parameter has a nonmonotonic character, displaying a sharp step, the positions of which on the concentration scale depends on the deposition temperature. A possible explanation of this phenomenon is suggested.